Effects of Obesity Induced by High-Fat Diet on the Pharmacokinetics of Atazanavir in Rats - Kobuchi, Shinji; Fukushima, Keizo; Aoyama, Hiroaki; Ito, Yukako; Sugioka, Nobuyuki; Takada, Kanji (Drug Metabolism Letters, 2013)
We studied the effects of obesity on the pharmacokinetics of atazanavir (ATV) using a rat model of high-fat diet-induced obesity (obese rats). The areas under the plasma concentration–time curves for intravenous bolus, oral, and intraportal administration of ATV in obese rats were significantly greater than the corresponding values in control rats. Total plasma clearance of ATV after intravenous bolus injection in the obese rats (0.80 ± 0.07 L/h/kg) was approximately half of that in the control rats (1.55 ± 0.18 L/h/kg). Furthermore, ATV concentration in the plasma-unbound fraction of the obese rats (4.2% ± 2.6%) was significantly lower than that in the control rats (14.2% ± 2.3%). Such differences may result in changes in ATV distribution from the systemic circulation to peripheral or central tissues, and the pharmacological effects of ATV may therefore be reduced in obese patients. Moreover, hepatic extraction in the obese rats (13.5% ± 1.6%) was approximately 62% of that in the controls (21.9% ± 0.96%). These results suggest that hepatic metabolism decreased and that dosing regimens should be carefully evaluated in obese patients. Therefore, in obese patients, it is necessary to pay careful attention to therapeutic drug monitoring data, and the use of specific dosing regimens, as well as that of monitoring system for liver fat accumulation are recommended.
Keywords: obesity